Insert Maranhao in Official Semi-Arid Geography: A Requirement of Social Justice in the Brazilian Northeast - Sousa Lemos, Jose de Jesus; Fernandes, Rachel Torquato [UNESP] (Univ Federal Espirito Santo, 2016)
The study attempts to show that the Brazilian semi-arid region is a region too needy. Even the Interior Ministry considering that there are municipalities only in the semiarid in eight of the Northeastern States excluding Maranhao, but incorporating municipalities in the state of Minas Gerais, the study also seeks to show that at least fifteen municipalities of Maranhao has semiarid features and these municipalities have some of the largest pockets of poverty in this Brazilian ecosystem. In order to achieve its objectives the study uses data collected by the State University of Maranhao, the Demographic Census of IBGE 2010 and the GDP of the municipalities published by the IBGE in 2012. They use the estimated drought indices in a previous study of the State University of Maranhao to the Maranhao municipalities supposed to possess technical characteristics of semiarid region. Social indicators are estimated such as education exclusion, income, running water, sanitation and garbage collection to all municipalities. The results showed that the average GDP of the semi-arid districts are much smaller than that of other municipalities in the Northeast. The ratio between the highest and the lowest GDP per capita in the semiarid region is 38.4. The iliteracv rates are high in all of them. Very high is also deprivation of access to piped water, sanitation and garbage collection also. The evidence of this study allow us to conclude that, in general, municipalities with technical characteristics of semi-arid in Maranhao State has economic, social and environmental indicators worse than the average of other municipalities already recognized in the Brazilian semiarid region.
Keywords: semiarid; social exclusion; environment